Hubungan Perhatian Orangtua dengan Motivasi Belajar Siswa - Ines Lidya Nandatama; Ratna Widiastuti; Redi Eka Adriyanto (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The purpose of this study was to determine the correlation between parental attention and students' learning motivation in the tenth grade of Public Senior High School 12 Bandar Lampung academic year of 2018/2019. The study applied descriptive method with product moment analysis. The population consisted of 323 students and a sample of 64 students taken through simple random sampling technique. The data collection techniques were carried out through parental attention scale and learning motivation scale. The results showed that there was a correlation between parental attention and students' motivation with a correlation value of r-count = 0.381 r-table = 0.244 at a significance level of 0.0,5 therefore Ho was rejected and Ha was accepted. The conclusion of this study is that there is a significant correlation between parental attention and students' learning motivation, it means that the greater the parental attention given to children the higher the students' motivation in learning.Tujuan Penelitian ini adalah untuk mengetahui hubungan antara perhatian orangtua dengan motivasi belajar siswa kelas X SMA Negeri 12 Bandar Lampung tahun pelajaran 2018/2019. Metode penelitian yang digunakan adalah analisis product moment. Populasi sebanyak 323 siswa dengan sampel berjumlah 64 siswa, diambil dengan teknik simple random sampling. Teknik pengumpulan data menggunakan skala perhatian orangtua dan skala motivasi belajar. Hasil penelitian menunjukkan bahwa ada hubungan anatara perhatian orangtua dengan motivasi belajar siswa dengan nilai korelasi r hitung = 0,381 r tabel= 0,244 pada taraf signifikansi 0,05 maka Ho ditolak da Ha diterima. Kesimpulan penelitian ini adalah terdapat hubungan signifikan antara hubungan perhatian orangtua dengan motivasi belajar siswa kelas X SMA Negeri 12 Bandar Lampung tahun pelajaran 2018/2019, artinya semakin besar perhatian yang diberikan orangtua pada anak maka akan semakin tinggi pula motivasi belajar siswa.Kata kunci: bimbingan dan konseling, perhatian orangtua, motivasi belajar